An analytical study on the content of selected websites for the science of Qirā’āt - Fatah Yasin, Raudlotul Firdaus; Zulkifli, Zati Syahmeena; Jani, Mohd Shah (2018)
Generally, people often use the Internet to search for information and this service is believed to be the most influential service In the context of learning the Science of Qirā’āt, this technology offers huge advantages for teachers and students. There are some websites that provide information on the Science of Qirā’āt including: http://www.kl.utm.my http://pmf.com.sg http://www.islamic-awareness.org http://www.alkeltawia.com http://www.tajweedinenglish.com http://islamweb.net http://www.youtube.com http://berandamadina.wordpress.com